The Effect of Self Talk Therapy to Change Negative Thinking Patterns in Students' Mathematics Learning - Dearni Anggita Damanik; Sri Ngayomi Yudha Wastuti (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
Previous research shows that the majority of students have a negative mindset towards learning mathematics, ranging from boredom, boredom, difficulty and uninteresting. This research aims to determine the effect of Self Talk Therapy to change the negative mindset in learning mathematics for class group guidance with a self-talk therapy approach. This research uses a quantitative approach, with a one group pretest-posttest design. The results of the research show changes in the negative mindset of students learning mathematics in the pre-test in the low category before being treated with group guidance services. There is a positive and significant difference in changes in students' negative mindset about learning mathematics in the post test after being treated with group guidance services with self-talk therapy. There is an influence of Self Talk Therapy to change the negative mindset of studying mathematics in class XI social sciences students at Muhammadiyah 1 Medan senior high school.